Rancang Bangun Aplikasi Steganografi dengan Metode Least Significant Bit di Audio pada Sistem Operasi Android - Lovebbi Lovebbi; Dodick Z. Sudirman (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2012)
Easy access to information this day, has increase the importance of security, especially private and secret information. the big amount of data transaction via smartphone without a proper data security has become a problem that needs attention. This paper’s goal is to implements steganography with least significant bit method for audio as alternative to data security. The implementations is done in Android operating system and produce an application for hiding message. This research proves that least significant bit in Android operating system fulfill the criteria of good steganography method. Keywords—data security, steganography, least significant bit, android